The effect of good corporate governance policies on welfare employee - Fauzi, Irsal; Barkhowa, Mokhammad Khukaim; Prasadhya, Ignatius Bias Galih (International Journal of Applied Finance and Business Studies, 2024)
The purpose of this study is to examine the influence of Good Corporate Governance based on Social Welfare Theory. The reason researchers choose Good Corporate Governance which is measured using Fairness, Disclosure/Transparency, Accountability and Responsibility Formulations is because this Formulation is very easy to apply at a practical level, and can more accurately measure the level of welfare received by Crew in the field, compared to other GCG formulations. This type of research is quantitative, with the main data source in the form of questionnaires, which will be analyzed using SEM PLS. Practically the application of GCG principles can help improve the welfare of the crew. The results showed that, Fairness, Transparency, Acoountability and Responsibility have a positive effect on the welfare of the crew. The recommendation in this study is, preferably between the Ministry of Transportation and the Ministry of Transportation, must carry out their functions and duties in accordance with the articles of association and laws and regulations, not dominate each other and throw responsibility on each other. This needs to be done, so that the goals and desires of the Crew in realizing their welfare get support and are well realized through the preparation of appropriate regulations.